2020
DOI: 10.2147/rmhp.s254928
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Relationship Among Organizational Identity, Psychological Resilience and Work Engagement of the First-Line Nurses in the Prevention and Control of COVID-19 Based on Structural Equation Model</p>

Abstract: Purpose To explore how the organizational identity and psychological resilience affect work engagement of the front-line nurses in the prevention and control of coronavirus disease 2019 (COVID-19) and to establish the relationship model based on these factors. Material and Methods Convenience sampling was applied to collect questionnaire samples from 216 nurses (from 12 cities in 6 provinces). General information questionnaires, organizational identity scale (OIQ), psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
61
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 36 publications
14
61
0
7
Order By: Relevance
“…A total of 191 articles were screened for inclusion criteria between the two searches; 32 were selected for this review (Figure 1 ). The studies were conducted from countries worldwide, including China ( n = 11) (Cai et al, 2020 ; Hu et al, 2020 ; Huang et al, 2020 ; Leng et al, 2020 ; Li et al, 2020 ; Liang et al, 2020 ; Lin et al, 2020 ; Liu et al, 2020 ; Lyu et al, 2020 ; Ou et al, 2020 ; Pang et al, 2021 ), Italy ( n = 1) (Catania et al, 2020 ), Iran ( n = 2) (Afshari et al, 2021 ; Meybodi & Mohammadi, 2020 ), France ( n = 1) (Altmayer et al, 2020 ), Japan ( n = 1) (Awano et al, 2020 ), Saudi Arabia ( n = 1) (Balay‐odao et al, 2021 ), the United States, ( n = 3) (Barzilay et al, 2020 ; LoGuidice & Bartos, 2021 ; Resnick, 2020 ), Singapore ( n = 1) (Goh et al, 2020 ), India ( n = 2) (Jose et al, 2020 ; Nathiya et al, 2021 ), Turkey ( n = 3) (Kılınç & Çelik, 2020 ; Yıldırım et al, 2020 ; Yörük & Güler, 2020 ), the Philippines ( n = 1) (Labrague & de los Santos, 2020 ), Canada ( n = 1) (Lapum et al, 2020 ), Spain ( n = 2) (Lorente et al, 2020 ; Luceño‐Moreno et al, 2020 ), the United Kingdom ( n = 1) (Roberts et al, 2021 ) and Ethiopia ( n = 1) (Tsehay et al, 2020 ). A summary of the articles included in this integrative review and their results can be found in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 191 articles were screened for inclusion criteria between the two searches; 32 were selected for this review (Figure 1 ). The studies were conducted from countries worldwide, including China ( n = 11) (Cai et al, 2020 ; Hu et al, 2020 ; Huang et al, 2020 ; Leng et al, 2020 ; Li et al, 2020 ; Liang et al, 2020 ; Lin et al, 2020 ; Liu et al, 2020 ; Lyu et al, 2020 ; Ou et al, 2020 ; Pang et al, 2021 ), Italy ( n = 1) (Catania et al, 2020 ), Iran ( n = 2) (Afshari et al, 2021 ; Meybodi & Mohammadi, 2020 ), France ( n = 1) (Altmayer et al, 2020 ), Japan ( n = 1) (Awano et al, 2020 ), Saudi Arabia ( n = 1) (Balay‐odao et al, 2021 ), the United States, ( n = 3) (Barzilay et al, 2020 ; LoGuidice & Bartos, 2021 ; Resnick, 2020 ), Singapore ( n = 1) (Goh et al, 2020 ), India ( n = 2) (Jose et al, 2020 ; Nathiya et al, 2021 ), Turkey ( n = 3) (Kılınç & Çelik, 2020 ; Yıldırım et al, 2020 ; Yörük & Güler, 2020 ), the Philippines ( n = 1) (Labrague & de los Santos, 2020 ), Canada ( n = 1) (Lapum et al, 2020 ), Spain ( n = 2) (Lorente et al, 2020 ; Luceño‐Moreno et al, 2020 ), the United Kingdom ( n = 1) (Roberts et al, 2021 ) and Ethiopia ( n = 1) (Tsehay et al, 2020 ). A summary of the articles included in this integrative review and their results can be found in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Overall, resilience scores among frontline healthcare workers during the COVID‐19 pandemic in the studies reviewed were in the moderate range (CD‐RISC range = 35.54–92.77) (Afshari et al, 2021 ; Cai et al, 2020 ; Jose et al, 2020 ; Kilinc & Celik, 2020; Leng et al, 2020 ; Li et al, 2020 ; Lin et al, 2020 ; Lyu et al, 2020 ; Nathiya et al, 2021 ; Ou et al, 2020 ; Pang et al, 2021 ). In two studies conducted in Asia, physicians had higher resilience scores than nurses (Awano et al, 2020 ; Lin et al, 2020 ), and support staff had the highest resilience scores (mean = 73.48) compared with doctors (mean = 67.78) and nurses (mean = 64.86) (Lin et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the COVID-19 pandemic, fostering resilience in nurses led to them having less fear of the disease and less psychological distress, emotional exhaustion and depression, as well as improving their quality of life (Labrague, 2021;Roberts et al, 2021;Yoruk & Guler, 2021). Other studies have associated resilience with sustained clinical performance and job engagement (Lyu et al, 2020). Further, resilience partially moderated the effects of the various pandemicrelated stressors on nurses' experience of psychological distress (Lorente et al, 2021).…”
mentioning
confidence: 96%